Novel receptor, mutation, vaccine, and establishment of coping mode for SARS-CoV-2: current status and future - Zeng, Zhaomu; Geng, Xiuchao; Wen, Xichao; Chen, Yueyue; Zhu, Yixi; Dong, Zishu; Hao, Liangchao; Wang, Tingting; Yang, Jifeng; Zhang, Ruobing; Zheng, Kebin; Sun, Zhiwei; et al. (Frontiers in Microbiology, 2023)
Since the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its resultant pneumonia in December 2019, the cumulative number of infected people worldwide has exceeded 670 million, with over 6.8 million deaths. Despite the marketing of multiple series of vaccines and the implementation of strict prevention and control measures in many countries, the spread and prevalence of SARS-CoV-2 have not been completely and effectively controlled. The latest research shows that in addition to angiotensin converting enzyme II (ACE2), dozens of protein molecules, including AXL, can act as host receptors for SARS-CoV-2 infecting human cells, and virus mutation and immune evasion never seem to stop. To sum up, this review summarizes and organizes the latest relevant literature, comprehensively reviews the genome characteristics of SARS-CoV-2 as well as receptor-based pathogenesis (including ACE2 and other new receptors), mutation and immune evasion, vaccine development and other aspects, and proposes a series of prevention and treatment opinions. It is expected to provide a theoretical basis for an in-depth understanding of the pathogenic mechanism of SARS-CoV-2 along with a research basis and new ideas for the diagnosis and classification, of COVID-19-related disease and for drug and vaccine research and development.